EVALUASI KINERJA KEUANGAN MENGGUNAKAN METODE DUPONT ANALYSIS - Dyah Shinta Kusumaningtyas; Novy Duwi Yanti; Joelianti Dwi Supraptiningsih (Universitas La Tansa Mashiro, 2025)
The rapid development of globalization has driven increasingly tight competition in the business world, including in the cosmetics and household needs sub-sectors listed on the Indonesia Stock Exchange (IDX). In the midst of these conditions, efficient financial management is an important factor in maintaining competitiveness and business sustainability. This study aims to evaluate the financial performance of companies in the cosmetics and household needs sub-sector for the period 2020–2024 using the DuPont Analysis method, which includes the Net Profit Margin (NPM), Total Asset Turnover (TATO), Return on Investment (ROI), and Return on Equity (ROE) ratios. The research method used is descriptive quantitative with a documentation approach to the annual financial reports of seven sample companies, namely PT Mustika Ratu Tbk, PT Martina Berto Tbk, PT Kino Indonesia Tbk, PT Victoria Care Indonesia Tbk, PT Mandom Indonesia Tbk, PT Akasha Wira International Tbk, and PT Unilever Indonesia Tbk. The results of the analysis show that PT Unilever Indonesia Tbk has the best financial performance with the highest ROE of an average of 142.26%, while PT Martina Berto Tbk shows the lowest performance with an average negative ROE of -80.54%.